Polychlorinated Biphenyl Levels and its Correlation to Size of Marine Organisms Harvested from a War-Induced Oil Spill Zone of the Eastern Mediterranean Sea - BARBOUR, E.K.; SABRA, A.H.; SHAIB, H.A.; BERCKLEY, A.M.; FARAJALLA, N.S.; ZURAYK, R.A.; HAMADEH, S.K.; KASSAIFY, Z.G. (Mediterranean Marine Science, 2009)
This is the first work establishing a base-line data of the level of total Polychlorinated Biphenyl (PCB) contaminants in selected marine organisms (Siganus rivulatus, Mullet spp., and oysters) and its relationship to organism size and the harvest distance from the oil spill source. Six locations across the Lebanese Mediterranean were included for sampling. Oysters and the two fish types were collected after 72 days of the spill. The length, maximum width, and whole weight of individual organisms were recorded. Methanol extracts of the samples were analyzed for total PCB using a Competitive Enzyme-linked Immunosorbent Assay (ELISA) based Spectrophotometry.All means of PCB in the three selected marine organisms were below the guidance level set by USFDA (2 ppm). A total of 6 significant regression equations were established between the total PCB level and certain size dimensions of specific selected marine species, with values of R2 ranging between 0.719 – 0.909 and P values ranging from 0.038 – 0.099.In addition, the total PCB level in Siganus rivulatus correlated with the harvest distance north of the oil spill source, signifying a drop in total PCB level with an increase in harvest distance from the oil spill source.